Effect of mineral and microbial fertilizers on the substrate microbiote under landing of generative plants of blueberries on the worked peatland of Belarus - Rupasova, Zhanna A.; Yakovlev, Alexander P.; Bulavko, Galina I.; Antokhina, Svetlana P.; Kolomiets, Emilia I.; Aleschenkova, Zinaida M. (Journal of the Belarusian State University. Ecology, 2020)
The article presents the results of a 3-years comparative research in experimental culture with generative plants Vaccinium angustifolium and varieties Northcountry and Northblue Vaccinium corymbosum seasonal dynamics of the main characteristics of the microbiota of the root peat layer of the peat substrate – biomass PAM, respiration rate and activity of metabolic processes against the background of N16P16K16 and «MaKloR» microbial fertilizers (in 10- and 50 % concentration), «AgroMik», «Bactopin» and «AMG» with differentiated and partly combined use. A significant dependence of the revealed regularities on the plant genotype, the level of mineral nutrition and the hydrothermal regime of the season has been established. The stimulating effect of the tested agricultural practices on the main characteristics of the microbiota was established. The most effective in terms of increasing the weight of actively functioning microorganisms was the joint use of «Baktopin» and «AMG» preparations, while the greatest activation of respiratory and metabolic processes was provided by applying N16P16K16, and under the planting of varietal blueberries also «AgroMik» liquid fertilizer.